2016
DOI: 10.2174/1566524016666160429121737
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing of Anti-Diabetic Agents for the Treatment of Cognitive Impairment and Mood Disorders

Abstract: Impairments in cognitive function represent a consistent, non-specific, and clinically significant feature in metabolic, mood, and dementing disorders. The foregoing observation is instantiated by evidence demonstrating that these disorders share pathophysiological mechanisms including, but not limited to, aberrant insulin signaling, inflammation, and glucocorticoid activity. Moreover, these mechanisms have been consistently reported to increase vulnerability to and/or exacerbate impairments in cognitive funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The studies in experimental models of the disease have led to clinical trials aimed at testing the efficacy of liraglutide in AD (ID: NCT01843075; ID: NCT01469351; ID: NCT02140983). Interestingly, liraglutide has been recently shown to improve cognition in individuals with mood disorders and Parkinson's disease . However, little is known to date about the cellular mechanisms of action of GLP‐1R agonists in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…The studies in experimental models of the disease have led to clinical trials aimed at testing the efficacy of liraglutide in AD (ID: NCT01843075; ID: NCT01469351; ID: NCT02140983). Interestingly, liraglutide has been recently shown to improve cognition in individuals with mood disorders and Parkinson's disease . However, little is known to date about the cellular mechanisms of action of GLP‐1R agonists in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that metformin can also penetrate the blood-brain barrier and protect neurons. Repurposing of anti-diabetic agents for the treatment of cognitive impairment and mood disorders has been proposed ( Cha et al, 2016 ).…”
Section: Ampk-ulk1 As a Therapeutic Targetmentioning
confidence: 99%
“…Metformin‐associated lactic acidosis is quite rare, with incidence estimated to be 3‐10 per 100,000 person‐years , and although quite rare, there are a few cases reports of rhabdomyolysis in the literature . Metformin is usually a first‐line medication in a patient with insulin resistance, prediabetes, or metabolic syndrome given the minimal safety concerns and tolerability. Though the meta‐analyses showed only a small reduction in excess weight in youth, metformin has been effective for weight regain related to antipsychotic medications in nondiabetic children (−4.1% weight reduction [95% CI: 2.2‐6.0]) and in adults, for weight gain related to mood disorders, steroid exposure, stress eating, and emotional eating related to cognitive dysfunction, possibly related to aberrant insulin signaling, inflammation, and glucocorticoid activity, which may be emanated by iatrogenic causes . Metformin is extensively utilized for polycystic ovarian syndrome treatment with or without obesity diagnosis in children and adolescents, with improvement seen on lipid profile, hirsutism, and weight loss . Off‐label drug‐use documentation, along with consent for treatment from the patient’s parent or guardian, is recommended. Effect of metformin on pubertal development is unknown.…”
Section: Recommendations (Table )mentioning
confidence: 99%